Gambaran Tingkat Pengetahuan Ibu Hamil Tentang HBsAg Pada Pemeriksaan VCT di Puskesmas Padang Pasir Kota Padang - Rizawati; Dian Eka Nursyam (Jurnal Amanah Kesehatan, 2022)
Hepatitis virus has caused 1.34 million deaths in 2015, Indonesia is the second largest country in Southeast Asia with high endemity of hepatitis B after Myanmar, prevention of HBsAg transmission from mother to child for HBsAg and hepatitis disease is carried out with the VCT test program which the VCT program namely Voluntary Counseling and Testing (VCT) or Voluntary Counseling and Testing (KTS) is an effective public health strategy for prevention as well as an entry point for case management services as well as care, support and treatment for people with positive hepatitis B. This study aims to describe the level of knowledge of pregnant women about HBsAg during VCT examinations in the Padang Pasir Padang Public Health Center. This research is descriptive in nature. The population of this study were all pregnant women in the Padang Pasir Community Health Center Work Area. The sample technique used was accidental sampling with a sample size of 45 people. The results showed that (48.9%) pregnant women had a low level of knowledge about the purpose of HBsAg on VCT examination, (66.7%) pregnant women had a low level of knowledge about the purpose of HBsAg on VCT examination, (33.3%) pregnant women have a low level of knowledge about the time of early detection of HBsAg in VCT examination, (55.6%) pregnant women have low level of knowledge about the benefits of HBsAg in VCT examination, (53.3%) pregnant women have low level of knowledge about how to do early detection of HBsAg on VCT examination. It is hoped that health workers will be more optimal in providing information to pregnant women about HBsAg on VCT examinations.